Effect of Maintenance Distance from Cooling Pad Against Average Increase Body Weight of Broiler Chickens in Closed House Cages - Irham Hafiz Mandiling; Tapaul Rozi; I Ketut Gede Wiryawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Broiler chickens are good genetic quality as seen from their fairly fast growth. An intensive and controlled cage system can be found in the closed house cage system. Based on the research, the average weight of harvested chickens is not uneven, possibly unequal distribution of fresh air entering through the inlet. This research aims to determine the effect of maintenance distance from the cooling pad on the average body weight growth of broiler chickens kept in closed house cages with a size of 98 X 14 m. as many as 16,000 broiler chickens of the CP 207 strain are randomly allocated into 4 groups or flocks. The distance of flocks 1, 2, 3 and 4 from the cooling pad is 0 -24.5, 24.6 - 49.5 and 49.6 - 73.5, and 73.6 - 98m respectively. The results showed a marked difference (P<0.05) in final body weight. The highest body weight was obtained at the closest distance to the cooling pad and the lowest weight was obtained in the chicken that was in the flock farthest from the cooolig pad. It was concluded that the chicken's body weight is lower the farther the flock is from the cooling pad.